Nagość w reklamie społecznej = Nakedness in social advertising - Bazuń, Dorota (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article is to present the ways of using nakedness in social advertising. 120 selected examples of social campaigns in which nakedness was used as a form of persuasion and communication were analysed. Qualitative methods of analysis were used (content analysis, visual sociology). Naked images in social advertising refer to the topics presented in the advertisement directly and indirectly. Nakedness is not always related to the subject and its functions are sometimes the same as in a commercial advertising - they should strengthen the positive connotations of the idea or organization. The article contains the author?s typology of the ways of using nakedness in social advertising. In social advertising authors often use a content and forms of communication that are intended to awake such emotions as aversion, shock or surprise. Images of young people are also presented more often. However, the images of their bodies are more naturalistic and more imperfect than in commercial advertising.
Keywords: ciało; płeć; nagość; reklama społeczna; kampania społeczna; body; gender; nakedness; social advertisement; social campaign